Study the Effect of Olibanum (Boswellia Carterii) on Hyperuricemia in Rat’s Module - mohammed, khairullah; Basim J. Hameed; Nadheerah Neamah (Iraqi Journal of Pharmaceutical Sciences, 2024)
A current investigation aimed to assess the antihyperuricemic activity of the Boswellia Carterii plant and investigate the action of urate-lowering effect in a rat pattern of hyperuricemia generated by potassium-oxonate. Rats used in the research were randomized into five groups (n=6). The rats in the negative group, allopurinol group, olibanum 50 mg/kg group, and olibanum 100 mg/kg group received intraperitoneal injections of potassium oxonate (PO) twice a week at a dose of 250 mg/kg. The normal control group was supplied food and drink without any intervention. As a positive one control group, the olibanum 50 mg/kg group received daily oral administration of 50 mg/kg of olibanum powder dissolved in 0.5 L of distal water, and the positive two olibanum 100mg/kg group treated with 100mg/kg of olibanum powder dispersed in 0.5L of distal water orally each day. Allopurinol (5mg/kg) was administered orally to rats in the allopurinol group daily. Each group’s animals were slaughtered, blood was taken, and serum was isolated for uric acid (UA) laboratory analysis and other biochemical parameters. Uric acid (UUA) and creatinine (UCr) in urine were also measured. The investigation results demonstrated a significantly substantial reduction in blood UA and modest inhibition of xanthine oxide (XOD) in rats with hyperuricemia that were given olibanum solution. Compared to the hyperuricemic control group, all groups showed non-significant variations in the kidney (Urea and CreaC) and liver (ALT, AlkP, and AST) functioning.